Gratitude Feelings of Involuntary Childless Couples - Octaviana, Shintha Tri; Septiningsih, Dyah Siti; Setyawati, Rr; Hamzah, Imam Faisal (Universitas Ahmad Dahlan, 2023)
Kebersyukuran pada Pasangan Involuntary ChildlessCouples who want children but cannot have them without intending to do so are said to be involuntarily childless. For the couple, it is not simple. Without a child, a husband and wife who are already married but are experiencing issues or emotions that force them to be childless can understand what gratitude means. Gratitude is one way that involuntarily childless couples can continue to support one another and remain hopeful about having children. This study aims to explore the meaning of gratitude in involuntary childless couples. This study employs a qualitative methodology and phenomenology. Semi-structured interviews, or interviews where the researcher has prepared the questions in advance using the idea of gratitude, are the data collection method. Three married couples with average marriage ages of 13 years, 12 years, and seven years, participated in this study. The study's findings demonstrate that Involuntarily childless couples are grateful for the help they receive from others and feel fortunate to have such support. Additionally, a childless couple always views their actions positively to feel grateful for Allah's blessings.